O carnaval contra as “ideias subversivas” e “ideologias exóticas”: a invenção da Federação Carnavalesca Pernambucana na década de 1930. // Carnival against “subversive ideas” and “exotic ideologies”:the invention Carnival Federation of Pernambuco during the 1930s. - Silva, Lucas Victor (2016)
Este artigo tem o objetivo de discutir o aparecimento da Federação Carnavalesca Pernambucana enquanto instituição comprometida com o controle das manifestações carnavalescas durante os anos 1930. Para tanto, analisamos as representações registradas na imprensa (Diário de Pernambuco, Jornal Pequeno, Jornal do Recife, A Província, Jornal do Commércio e Diário da Manhã) e na documentação produzida pela própria entidade. O carnaval emerge como instrumento das tentativas de naturalização das hierarquias sociais e da demonstração da coesão nacional e da unidade do repertório cultural do país.This article aims to discuss the emergence of the Carnival Federation of Pernambuco as an institution committed to the control carnival displays during the 1930s. In this sense, the representations registered in both the local press (the Diário de Pernambuco, Jornal Pequeno, Jornal do Recife, A Província, Jornal do Commercio and Diário da Manhã newspapers) and the documentation produced by the institution itself have been analyzed. Carnival, as an object of discourse, emerges as an instrument of the attempts carried out by the post-1930 political regime to, through the speech of its intellectuals, produce the acceptance of the new regime and demonstrate national cohesion and the unity of the cultural repertoire of Brazil.